Rain fade slope model for terrestrial microwave links - Chebil, Jalel; Islam, Md Rafiqul; Zyoud, Al-Hareth; Habaebi, Mohamed Hadi; Dao, Hassan (Cambridge University Press, 2020)
The dynamic characteristic of rain fade slope is one important factor in determining the availability of a communication system, and it is very useful in the design of fade countermeasures. In the literature, many models were proposed for rain fade slope for earth-to-satellite links. However, there are no models available for rain fade point to point terrestrial microwave links. This paper proposes a new model for the estimation of rain fade slope statistics for terrestrial microwave links in tropical regions. First, the ITU-R model for rain fade slope for earth-to-satellite link was compared with the corresponding statistics obtained from rain attenuation data measured from three terrestrial links in Malaysia. It is found that the expression of its distribution and its standard deviation should be modified. This leads to the derivation of the proposed rain fade slope model based on the statistics of one link. Then, it is tested using the remaining data and its results were very close to the measured statistics for all attenuation levels higher than 1 dB. Moreover, the model was validated using the chisquare goodness-of-fit test.